PENGARUH CORPORATE SOCIAL RESPONSIBILITY DAN GOOD CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL MODERASI - Soedarman, Mohammad; Putri, Margaretha Yetria; Sa'adah, Lailatus (Inspirasi Ekonomi : Jurnal Ekonomi Manajemen, 2024)
This research aims to determine the influence of Corporate Social Responsibility and Good Corporate Governance on company value with profitability as a moderating variable in telecommunications companies that are listed on the Indonesia Stock Exchange (BEI) in the 2019-2021 period. The data used in this research is secondary data. Research data analysis uses Partial Least Square (PLS) using a structural model (Inner Model). The independent variables in this research are Corporate Social Responsibility and Good Corporate Governance, the dependent variable in this research is company value. Using the purposive sampling method as a sampling technique, with a population of 19 companies. In this research, 15 telecommunication companies were used as samples. The results of this research show that: (1) CSR has no effect on company value, (2) GCG has a significant effect on company value, (3) profitability cannot moderate the relationship between CSR and company value, (4) Profitability cannot moderate the relationship between GCG and value company.